Longitudinal positron emission tomography imaging of glial cell activation in a mouse model of mesial temporal lobe epilepsy: Toward identification of optimal treatment windows. (19th April 2018) - Nguyen, Duc‐Loc; Wimberley, Catriona; Truillet, Charles; Jego, Benoit; Caillé, Fabien; Pottier, Géraldine; Boisgard, Raphaël; Buvat, Irène; Bouilleret, Viviane
Summary: Objective: Mesiotemporal lobe epilepsy is the most common type of drug‐resistant partial epilepsy, with a specific history that often begins with status epilepticus due to various neurological insults followed by a silent period. During this period, before the first seizure occurs, a specific lesion develops, described as unilateral hippocampal sclerosis (HS). It is still challenging to determine which drugs, administered at which time point, will be most effective during the formation of this epileptic process. Neuroinflammation plays an important role in pathophysiological mechanisms in epilepsy, and therefore brain inflammation biomarkers such as translocator protein 18 kDa (TSPO) can be potent epilepsy biomarkers. TSPO is associated with reactive astrocytes and microglia. A unilateral intrahippocampal kainate injection mouse model can reproduce the defining features of human temporal lobe epilepsy with unilateral HS and the pattern of chronic pharmacoresistant temporal seizures. We hypothesized that longitudinal imaging using TSPO positron emission tomography (PET) with 18 F‐DPA‐714 could identify optimal treatment windows in a mouse model during the formation of HS. Methods: The model was induced into the right dorsal hippocampus of male C57/Bl6 mice. Micro‐PET/computed tomographic scanning was performed before model induction and along the development of the HS at 7 days, 14 days, 1 month, and 6 months. In vitro autoradiography and immunohistofluorescence were performed on additional mice at each time point. Results: TSPO PET uptake reached peak at 7 days and mostly related to microglial activation, whereas after 14 days, reactive astrocytes were shown to be the main cells expressing TSPO, reflected by a continuing increased PET uptake. Significance: TSPO‐targeted PET is a highly potent longitudinal biomarker of epilepsy and could be of interest to determine the therapeutic windows in epilepsy and to monitor response to treatment.